bonjour je dois calculer les expression suivantes
A = -3(-5)+6+(-1)+12+8
B = 9+(-5)+6+9+(-7)+(-2)
C = 0.1+0.5+(-0.4)+0.8+(-0.6


Sagot :

Bonjour


calculer les expression suivantes 


A = -3(-5)+6+(-1)+12+8

A = -3 x (-5) + 6 - 1 + 12 + 8

A = 15 + 6 + 12 + 8 - 1

A = 41 - 1

A = 40

B = 9+(-5)+6+9+(-7)+(-2)

B = 9 - 5 + 6 + 9 - 7 - 2

B = 9 + 6 + 9 - 5 - 7 - 2

B = 24 - 14

B = 10


C = 0.1+0.5+(-0.4)+0.8+(-0.6

C = 0,1 + 0,5 - 0,4 + 0,8 - 0,6

C = 0,1 + 0,5 + 0,8 - 0,4 - 0,6

C = 1,4 - 1

C = 0,4